2011
DOI: 10.3109/01612840.2011.609634
|View full text |Cite
|
Sign up to set email alerts
|

Becoming a Psychiatric/Mental Health Nurse in the UK: A Qualitative Study Exploring Processes of Identity Formation

Abstract: Identity studies are well established across the social science literature with mental health nursing beginning to offer evidenced insights into what may, or may not, constitute key identity performances. For mental health nursing these performances remain contested, both from within the profession and from international contexts that favour generic constructions of mental health. This paper offers findings from a qualitative study that focused upon the process of how mental health nursing identity development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 27 publications
0
21
0
4
Order By: Relevance
“…Since the reform of nursing education in Australia in the 1990s, specialist qualifications are no longer required for nursing practice in mental health settings (Happell, 2006;Hurley & Lakeman, 2011), resulting in it being undervalued (Happell & Cutcliffe, 2011). The emphasis on the need for mental health nursing qualifications likely reflects the concern that professional identity may be otherwise further weakened.…”
Section: Discussionmentioning
confidence: 97%
“…Since the reform of nursing education in Australia in the 1990s, specialist qualifications are no longer required for nursing practice in mental health settings (Happell, 2006;Hurley & Lakeman, 2011), resulting in it being undervalued (Happell & Cutcliffe, 2011). The emphasis on the need for mental health nursing qualifications likely reflects the concern that professional identity may be otherwise further weakened.…”
Section: Discussionmentioning
confidence: 97%
“…Formal education is often the mechanism for increasing confidence, which in turn becomes a characteristic of a mental health nurse's identity, for example by extending the repertoire of interventions to offer service users (Hurley & Lakeman, 2011). As this was a pilot study, it offers useful insights for the planning of future courses.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors argue that generalist nursing programmes result in a reduction of career choice paths, especially those into mental health work. Indeed it is suggested that specialisation makes a major contribution to recruitment and retention (Hercelinskyi, 2013;Hurley et al, 2011;Hurley & Ramsay, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…At present pre-registration nurse education has a generic core, with mental health clinical experience making up 50% of the whole course (2,300 hours of 4,600 hours), highlighting the value of learning in the workplace, a fundamental aspect for nursing students to assume the identity and skills of mental health nursing (Hurley & Lambert Hemmingway 2016Lakeman, 2011. Many authors argue that generalist nursing programmes result in a reduction of career choice paths, especially those into mental health work.…”
Section: Introductionmentioning
confidence: 99%